PENGARUH KEMAMPUAN KERJA, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PAGAWAI INSPEKTORAT KABUPATEN BELITUNG - Sudirman, Iman; Dallyodi, Mirza (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2021)
The results of preliminary studies had findings that employee performance is not optimal. Of the many factors causing encountered, allegedly the most dominant in terms of employability, work motivation and discipline are still low. Therefore, the problem is formulated covering; how the work ability, motivation, and discipline. How big is the direct and indirect influence of work ability, motivation, and discipline to employee performance Inspectorate Belitung. While research method used is descriptive method of analysis, conducted on all employees, ie all members of the population has an equal opportunity to study and overall with a total of 46 employees serve as the respondents (survey). The data analysis technique used is the technique of correlation analysis is to determine the degree of closeness of the relationship between the study variables and Technical Analysis Path. The results of this study indicate that there is a significant relationship between work ability, motivation and discipline work individually or jointly on the performance of employees. Conclusions from the study indicate that the ability to work, work motivation, and discipline prevailing at this time significantly influence employee performance by 77.30% while the remaining 22.70% influenced by other factors not examined. Based on the research results presented some suggestions include: The need for efforts to improve the ability of employees working in accordance with the duties of the employee Inspectorate Belitung province, either through formal education as well as education and training organized by the Government of Belitung; Need to be increased their encouragement, given the opportunity and the award commensurate not only shaped material, for employees in the execution of his job duties; Needs to be improved and applied strict rules to provide certain sanctions to employees who lack discipline; Need mengopltimalkan employee performance, to push employees to be able to fulfill his job through the quantity, quality and time of completion of the work which has been determined leadership and to all employees of the Inspectorate Belitung province, continue to optimize the required work ability, motivation, and discipline to employee performance , in order to achieve organizational goals with good and services to the public will soon feel the benefits.